1957 La Torre - San Jose State College:::Creator:::; Kilpatrick, Ron:::Contributor:::
Centennial edition. The annual yearbook included photographs and stories covering the school year's events, class members, student organizations, student clubs, student societies, faculty members, and sports. Earlier issues also included poetry and humorous stories and anecdotes. This centennial edition also includes information on the history of the college, as well as photographs of the college from the past one hundred years.